Heredopatia atática polineuritiforme Heredopathia atactica polyieuritiformis - A. Spina-França; A. Anghinah; L. C. Mattosinho-França (Arquivos de Neuro-Psiquiatria)
Registro de caso de paciente com quadro mórbido relacionável ao da heredopatia atática polineuritiforme (doença de Refsum). O diagnóstico é discutido frente aos aspectos clínicos, laboratoriais e histopatológicos encontrados e sua relação com os achados referidos na literatura como próprios a essa moléstia. The case of a patient with many of the clinical characteristics commonly referred to in Refsum's disease is reported. Ichthyosis was noted in the patient and in other members of the family. Cerebrospinal fluid proteins were normal. Serum copper and caeruloplasmin concentrations were hight, as well as transaminases. Histological findings common to neuritis interstitialis hypaertrophica were found on examination of a peripheric nerve segment obtained by biopsy. Studies on the occurrence of phytanic acid could not be carried out. The relationship between the case reported and Refsum's syndrome is discussed.